Acceleration method for accurately simulating corrosion of metal material in atmospheric environment
Through the parameter design of corrosion tests of metal materials, especially moisture and heat tests and salt spray tests, the specific relationship is met, and the problem of inaccurate corrosion simulation of metal materials in the atmospheric environment in the prior art is solved, achieving more accurate corrosion prediction and reducing test costs.
Patent Information
- Application Number
- CN202411710696.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to accurately simulate the corrosion of metal materials in the atmospheric environment, and the accelerated test parameters are inaccurate, resulting in inaccurate corrosion prediction and increase the test cost and cycle.
By designing different test stage sequences and experimental parameters of corrosion tests, especially humidity and heat tests and salt spray tests, the test parameters can meet specific relationships, and accurately simulate corrosion of metal materials in the atmospheric environment is achieved.
It significantly improves the proximity between the accelerated corrosion results and the actual corrosion results, estimates the service life of the material more accurately, and reduces the test cost and cycle.
Smart Images

Figure CN119574414A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of accelerated testing, in particular to a method for accurately simulating the acceleration of corrosion of metal materials in an atmospheric environment. Background Art
[0002] The power facilities and equipment system is huge, covering all aspects from power transmission to distribution, to balance supply and demand and improve energy efficiency. The above-mentioned key facilities and equipment of the power system, except for certain small, non-structural components, are widely constructed of metal materials such as copper, iron, and aluminum. With its excellent conductivity, mechanical strength and cost-effectiveness, it has become the cornerstone of the power industry. However, when metal parts are exposed to harsh environments for a long time, such as heavily polluted atmosphere, salt-rich soil, or water sources containing corrosive chemicals, they will suffer from severe corrosion erosion, and the operation of power system equipment will cause vibration, which will affect the corrosion rust layer and cause the rust layer to peel off. Corrosion not only directly damages the material structure and shortens the service life of the equipment, but may also cause equipment failure, resulting in power outages, and seriously reducing the reliability and stability of the power system. Therefore, a scientific and comprehensive assessment of the corrosion status of power grid materials has become an indispensable part of ensuring the safe, efficient and reliable operation of power system facilities and equipment.
[0003] Through the accelerated corrosion test method, potential corrosion risks can be discovered and prevented in a timely manner, providing a scientific basis for equipment maintenance and replacement, effectively reducing economic losses and social impacts caused by corrosion, ensuring the continuity and stability of power supply, and providing a solid energy guarantee for the sustainable development of the economy and society.
[0004] Accurately confirming the test parameters for accelerated corrosion can not only accurately predict the service life of power system materials, but also reduce test costs. Summary of the invention
[0005] The purpose of the present invention is to provide a method for accelerating the corrosion of metal materials in an atmospheric environment. The present invention can accurately simulate the corrosion of materials in an atmospheric environment and accurately predict the service life of materials by accurately controlling the experimental conditions.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a method for accurately simulating the corrosion acceleration of metal materials in an atmospheric environment, comprising the following steps:
[0008] S0 is the temperature and humidity data of the real atmospheric environment where the sample is located;
[0009] S1 sample pretreatment;
[0010] S2 placing the pretreated sample in a simulated environment for a periodic corrosion test, wherein the periodic corrosion test has a cycle of "wet heat test → drying test → salt spray test → drying test → vibration test";
[0011] S3: The sample corroded in step S2 is post-processed to obtain a sample to be tested, and the surface corrosion morphology, corrosion rate and electrochemical performance of the sample to be tested are analyzed;
[0012] Among them, in the periodic corrosion test, the time of each test satisfies the following relationship:
[0013]
[0014] t 盐雾 Indicates the time of salt spray test, in h;
[0015] t 湿热 Indicates the time of the damp heat test, in h;
[0016] T k represents the temperature of the real atmospheric environment at time k, in °C;
[0017] T 试验 Indicates the preset temperature during the test, in °C, T 试验 =T 湿热 =T 盐雾 ;
[0018] RH k Represents the humidity of the real atmospheric environment at time k, in %;
[0019] RH 试验 Indicates the preset humidity during the damp heat test, in %;
[0020] n represents the humidity coefficient;
[0021] Ea represents activation energy;
[0022] R represents the ideal gas constant;
[0023] α represents the corrosion acceleration factor of the salt spray test.
[0024] The inventors of the present invention have conducted a large number of experiments combined with real temperature and humidity meteorological data of the environment, and found that by designing the order of different test stages of corrosion tests and the experimental parameters of different corrosion tests, especially the damp heat test and salt spray test that play a key role in accelerating corrosion, so that the test parameters satisfy a specific relationship, the degree of proximity between the accelerated corrosion results and the actual corrosion results can be significantly improved, the service life of the material can be more accurately estimated, and the test cost and test cycle can be reduced.
[0025] It should be noted that, in the above formula, 8760 represents the number of hours in a year.
[0026] In the accelerated corrosion test of the present invention, T 试验 =T 湿热 =T 盐雾 .
[0027] Preferably, the material of the sample includes but is not limited to Q235 carbon steel, T2 copper or 6061 aluminum alloy.
[0028] Preferably, the conditions of the damp heat test are: temperature of 40±3°C; humidity of 90±5%; and time of 7-10h in one cycle.
[0029] Preferably, the conditions of the salt spray test are: temperature 40±3°C, salt spray deposition 1.0-1.5mL / (mm 2 ·h), within one cycle, the spraying time is 8-12h.
[0030] The composition of the spray liquid for the salt spray test includes: 0.05-0.2wt% NaCl, 0.05-0.2wt% Na2SO4, and the balance is water.
[0031] Preferably, the conditions of the drying test are: temperature of 40±3° C. and humidity of 20-30%. Under such conditions, the sample can be ensured to be completely dry during the switching process of the corrosion module.
[0032] Preferably, in the periodic corrosion test, the time relationship of each test stage further satisfies:
[0033] t 盐雾 +t 湿热 +t 干燥 =360h.
[0034] Preferably, the conditions of the vibration test are: frequency cycle range is (3-8) Hz→(30-35) Hz→(3-8) Hz; sweep rate is (0.5-1.0) oct / min; drive amplitude is 0.15-0.25 mm, and vibration time is 3-15 min.
[0035] Preferably, the pretreatment includes sample preparation, surface cleaning and drying. Specifically: (a) the sample obtained by sample preparation is in the form of flakes; (b) the surface cleaning is processed to a smoothness Ra ≥ 3.2, degreased and cleaned with a degreasing agent, and then further dehydrated with ethanol; (c) drying is performed at 25±5°C for > 24h.
[0036] Preferably, in step S2, in the periodic corrosion test, the number of cycles is ≥15.
[0037] Preferably, the post-treatment in step S3 is to rinse the surface with alcohol and dry it with a hair dryer.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The present invention designs the sequence of different test stages of the corrosion test and the experimental parameters of different corrosion tests, especially the wet heat test and the salt spray test which play a key role in accelerating corrosion, so that the test parameters satisfy a specific relationship, which can significantly improve the degree of proximity between the accelerated corrosion result and the actual corrosion result, more accurately estimate the service life of the material, and reduce the test cost and test cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 In the corrosion tests of different materials, (a) to (c) are scanning electron microscope microscopic morphologies of the surface of Q235 carbon steel specimens after 1 week (a), 2 weeks (b), and 3 weeks (c) of cyclic corrosion, respectively; (d) to (f) are scanning electron microscope microscopic morphologies of T2 copper specimens after 1, 2, and 3 weeks of cyclic corrosion; (g) to (h) are scanning electron microscope microscopic morphologies of 6061 aluminum alloy specimens after 1, 2, and 3 weeks of cyclic corrosion. DETAILED DESCRIPTION
[0041] For better explanation of the purpose, technical scheme and advantage of the present invention, the present invention will be further described below in conjunction with specific embodiment and accompanying drawing, but embodiment does not limit the present invention in any form.Unless otherwise specified, the reagent, method and equipment adopted in the present invention are conventional reagents, methods and equipment in the art.Unless otherwise specified, the reagents and materials used in the present invention are commercially available.
[0042] In the embodiments and comparative examples of the present invention, the spray liquid used in the salt spray test contains 0.1 wt % NaCl and 0.1 wt % Na2SO4.
[0043] Examples 1-3, Comparative Examples 1-2
[0044] A series of methods for simulating the accelerated corrosion of metal materials in an atmospheric environment are provided, including the following steps:
[0045] S1 Sample pretreatment
[0046] Q235 carbon steel (composition see Table 1) was used as the sample, and processed into a sheet sample of 5cm*2.5cm and 2mm thickness, and then ground and polished to the surface finish of the sample Ra≥3.2, and the sample was degreased and dehydrated with ethanol, cleaned, and dried with a hair dryer, and the initial test mass m0 (in g) of the sample was weighed;
[0047] Table 1 Composition of Q235 carbon steel
[0048]
[0049] S2 performs periodic corrosion test: the sample pretreated in step S1 is placed in a simulated environment and subjected to periodic test, each periodic test includes the following tests in sequence: wet heat test → drying test → salt spray test → drying test → vibration test;
[0050] Among them, in the vibration test, within one vibration cycle, the test conditions are: scanning rate is 1.0 oct / min, amplitude is 0.20 mm, cycle frequency is: 5 Hz, 164s→33 Hz, 164s→5 Hz, 164s→33 Hz, 164s→5 Hz, ... and so on, vibrating for 15 minutes;
[0051] The conditions of the drying test are: temperature 40℃; humidity 30%; during the entire periodic corrosion test, the corrosion time meets: t 盐雾 +t 湿热 +t 干燥 = 360h; unless otherwise specified, in the embodiments of the present invention, the conditions of the two drying tests in one periodic test are the same;
[0052] The test conditions of other stages are detailed in Table 2;
[0053] Table 2
[0054]
[0055]
[0056] Note: In the relationship, n = 3, n represents the humidity coefficient, Ea represents the activation energy, which is 52110 J / mol, and R represents the ideal gas constant, which is 8.314 J / (mol·K).
[0057] About T k and RH k It should be noted that these two parameters are the data collected from the real atmospheric environment, which is the actual environmental data for a total of 8760 hours a year. k and RH k Enter the environmental data collected in the first hour, 20℃, 70%; the test temperature / humidity is 40℃, 90%,
[0058] By calculation,
[0059] It shows that the sample is corroded in a 20℃, 70% environment for 1 hour, and we can achieve the same corrosion effect by corroding in a 40℃, 90% environment for 0.12 hours. This is only the calculation of the first hour. If we bring in all 8760 hours, we can calculate the time it takes to achieve a one-year corrosion effect through a 40℃, 90% environment test.
[0060] S3 Corrosion Analysis
[0061] (1) Surface corrosion micromorphology: The corrosion micromorphology was observed using a scanning electron microscope (SEM). Figure 1 (ac); It can be seen from the figure that the corrosion products are relatively flat, but there are also local pitting corrosion products on its microscopic surface. This is because as the test progresses, the pitting corrosion products on its surface turn into needle-like or fibrous structures, and then the volume of the needle-like corrosion products increases, and the rust layer tends to become flat.
[0062] (3) Corrosion rate analysis of materials:
[0063] The sample after corrosion in step S2 is cleaned of corrosion products on the surface of the sample according to the corrosion product removal standard in the standard "GB / T16545-2015 Corrosion of Metals and Alloys", and the surface is rinsed with alcohol and dried with a hair dryer to obtain a sample to be tested. The corrosion condition of the sample to be tested is analyzed as follows:
[0064] Measure the weight m of the sample at different times during the corrosion process, and calculate the corrosion thickness loss of the sample using the following relationship:
[0065]
[0066] d is the corrosion thickness loss, μm;
[0067] m0 is the initial weight of the sample, g;
[0068] m is the weight of corrosion products removed from the sample after the corrosion test, g;
[0069] A is the surface area of the sample, which is 2800 mm 2 ;
[0070] ρ is the density of the sample, g / mm 3 ;
[0071] Then, with time n as the horizontal coordinate and thickness loss as the vertical coordinate, the curve was fitted with a function to obtain the corrosion curve. It was found that the thickness loss and corrosion time satisfy the relationship: d = 34.4 × n 0.83 , d represents the thickness loss of the sample at a certain moment (in μm), and n represents the actual corrosion time in the atmospheric environment after conversion (in years).
[0072] Example 2 is used as an example: the total salt spray time is 165.3h, the wet heat time is 104.7h, and the drying time is 90h. The above test is carried out for 15 days; the salt spray time per day = 165.3 / 15 = 11h, the wet heat time = 104.7 / 15 = 7h, and the drying time = 90 / 15 = 6h; the final test composition is: (11h salt spray + 3h drying + 7h wet heat + 3h drying + 15min vibration) * 15 cycles = 1 simulated corrosion test cycle. After 15 cycles, we can evaluate the corrosion amount in one year (n = 1).
[0073] It can be seen that the fitting relationship is an exponential function, which is more consistent with the corrosion in the actual atmospheric environment.
[0074] Embodiment 4-5
[0075] This embodiment provides a series of methods for accurately simulating the acceleration of corrosion of metal materials in an atmospheric environment. The test is performed with reference to the method of Embodiment 1. The difference from Embodiment 1 is that the materials of the samples are replaced with T2 copper (Embodiment 4) and 6061 aluminum alloy (Embodiment 5). The materials and compositions of the samples are detailed in Tables 3 and 4.
[0076] Table 3 Alloy composition of T2 copper
[0077]
[0078] Table 4 Alloy composition of 6061 aluminum alloy
[0079]
[0080] In the corrosion analysis of step S3, the surface microstructure is similar to that of Example 1, and the fitting curves of the corrosion thickness loss of T2 copper are d=0.91×n 0.67 , the fitting curves of corrosion loss of 6061 aluminum alloy are d=8.70×n 0.46 , which is also an exponential function and is close to the actual corrosion situation.
[0081] Comparative Example 3
[0082] This comparative example provides a series of methods for accurately simulating the acceleration of corrosion of metal materials in an atmospheric environment. The test is carried out with reference to the method of Example 1. The difference from Example 1 is that no vibration test is carried out, and the fitting curve of the corrosion loss is d=12.8×n+0.72, which is somewhat different from the actual corrosion rate trend. The degree of fit with the actual situation is high only in a short period of time, which is not conducive to corrosion prediction for a longer period of time.
[0083] Furthermore, the present invention also compares the corrosion performance predicted by the accelerated corrosion curve obtained from the accelerated corrosion test with the corrosion performance of the sample in the real atmospheric environment, as shown in Table 4:
[0084] Table 4
[0085]
[0086] In Table 4, it can be seen from the analysis of the corrosion results of the embodiments and comparative examples that:
[0087] The accelerated corrosion test of the present invention is closer to the corrosion in the actual environment, and can quickly and accurately determine the test parameters, thus saving the cost of simulating corrosion and improving the prediction accuracy.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for accurately simulating the corrosion acceleration of metal materials in an atmospheric environment, characterized in that: The following steps are involved: S0 collects the temperature and humidity data of the real atmospheric environment where the sample is located; S1 sample pretreatment; S2: placing the pretreated sample in a simulated environment for a periodic corrosion test, wherein the periodic corrosion test has a cycle of "wet heat test → drying test → salt spray test → drying test → vibration test"; S3: The sample corroded in step S2 is post-processed to obtain a sample to be tested, and the surface corrosion morphology, corrosion rate and electrochemical performance of the sample to be tested are analyzed; Among them, in the periodic corrosion test, the time of each test satisfies the following relationship: t 盐雾 Indicates the time of salt spray test, in h; t 湿热 Indicates the time of the damp heat test, in h; T k represents the temperature of the real atmospheric environment at time k, in °C; T 试验 Indicates the preset temperature during the test, in °C, T 试验 =T 湿热 =T 盐雾 ; RH k Represents the humidity in the real atmospheric environment at time k, in %; RH 试验 Indicates the preset humidity during the damp heat test, in %; n represents the humidity coefficient; Ea represents activation energy; R represents the ideal gas constant; α represents the corrosion acceleration factor of the salt spray test.
2. The method for accelerating the accurate simulation of corrosion of metal materials in an atmospheric environment according to claim 1, characterized in that: The conditions of the damp heat test are: temperature of 40±3°C and humidity of 90±5%.
3. The method for accelerating the accurate simulation of corrosion of metal materials in an atmospheric environment according to claim 1, characterized in that: The composition of the spray liquid for the salt spray test includes: 0.05-0.2wt% NaCl, 0.05-0.2wt% Na2SO4, and the balance is water.
4. The method for accelerating the accurate simulation of corrosion of metal materials in an atmospheric environment according to claim 3, characterized in that: The conditions of the salt spray test are: temperature 40±3°C, salt spray deposition 1.0-1.5mL / (mm 2 h).
5. The method for accelerating the accurate simulation of corrosion of metal materials in an atmospheric environment according to claim 1, characterized in that: The conditions of the drying test are: temperature of 40±3° C. and humidity of 20-30%.
6. The method for accelerating the accurate simulation of corrosion of metal materials in an atmospheric environment according to claim 1, characterized in that: The conditions of the vibration test are: frequency cycle range is (3-8) Hz→(30-35) Hz→(3-8) Hz; sweep rate is (0.5-1.0) oct / min; drive amplitude is 0.15-0.25 mm; vibration time in a single cycle is 3-15 min.
7. The method for accelerating the accurate simulation of corrosion of metal materials in an atmospheric environment according to claim 1, characterized in that: The pretreatment includes sample preparation, surface cleaning and drying.
8. The method for accelerating the accurate simulation of corrosion of metal materials in an atmospheric environment according to claim 1, characterized in that: The post-treatment includes alcohol washing and drying.
9. The method for accelerating the accurate simulation of corrosion of metal materials in an atmospheric environment according to claim 1, characterized in that: In the periodic corrosion test, the cycle period is ≥15.
10. The method for accelerating the accurate simulation of corrosion of metal materials in an atmospheric environment according to claim 1, characterized in that: The materials of the samples include Q235 carbon steel, T2 copper or 6061 aluminum alloy.
Citation Information
Patent Citations
Accelerated test method for simulating atmospheric corrosion of metal materials
CN101738365A
Accelerated corrosion test method for simulating salt spray environment for carbon steel
CN114720359A
Accelerated test method and device for equipment life, storage medium and electronic equipment
CN117313316A
Design method, experimental method and device for accelerated corrosion test
CN118706722A
Accelerated corrosion test method for bridge steel materials
JP2024010478A